WAP-Based Youth Referendum System (WYRS) - Eldenfria, Atef Hamza (2008)
The WAP-based youth referendum system (WYRS) uses WAP technology that can be obtained easily. It is flexible way to access the information at any time from any location. This research introduces a WAP application that provides the rural people with the avenue for referendum. Many people in these areas do not have opportunity to discuss and vote issues relevant to them. This service will provide people access to information and give them a chance to have a say in policies. Using this technology, rural people can easily get necessary information about the voting information, and get involved in voting on issues, making them part of the nation building.